A Case of Neglected Bilateral Anterior Shoulder Dislocation: A Rare Entity with Unusual Mechanism of Injury - Raghuram Choulapalle; Ramu Chokkarapu; Ravi Kanth Kolluri; Sreedhar Reddy Anne; Shanmuga Raju Perumal; Pavan Kumar Avadhanam; Ramesh Bheemanathuni (Case Reports in Orthopedics)
Bilateral shoulder dislocations are rare, and if they occurred, posterior type of dislocations is common. Bilateral anterior shoulder dislocations are very rare and occur due to trauma with unique mechanism of injury. We report a case of unreduced simultaneous bilateral anterior dislocations of shoulder without associated fractures in a forty-year-old man following a unique mechanism of injury; both hands of the patient were pulled from either side. To the best of our knowledge, this unusual mechanism of injury has not been reported in the literature.